Interleukin‐2‐inducible Killer Activity and Its Regulation by Blood Monocytes from Autologous Lymphocytes of Lung Cancer Patients - Sone, Saburo; Kunishige, Eiji; Fawzy, Farid; Yanagawa, Hiroaki; Nil, Akihiko; Maeda, Ken‐ichi; Atagi, Shinji; Heike, Yuji; Nishioka, Yasuhiko; Mizuno, Kazuhito; Ogura, Takeshi (Cancer science, 1991)
The ability of blood lymphocytes of newly diagnosed lung cancer patients to respond to interleukin 2 (IL‐2) to become IL‐2‐activated killer (LAK) cells and its regulation by autologous monocytes were examined. LAK activity was measured by 31Cr release assay. The abilities of lymphocytes among blood mononuclear cells (MNC) of subjects of different ages without malignancies to generate LAK activity against NK‐cell resistant Daudi cells and lung adenocarcinoma (PC‐9) cells were very similar. The LAK activity of blood MNC of lung cancer patients was also nearly the same as that of blood MNC of control subjects. There was no significant difference in IL‐2‐inducible LAK activity between MNC of patients with small cell lung cancer (SCLC) and those of patients with non‐SCLC. Monocytes and lymphocytes were separated from blood MNC on a one‐step Percoll gradient. Monocytes of lung cancer patients were found to augment in vitro induction of LAK activity by IL‐2 of autologous blood lymphocytes. In contrast, endotoxin‐stimulated monocytes suppressed LAK induction of autologous lymphocytes of cancer patients. These findings suggest that administration of IL‐2 and LAK cells induced in vitro may be of benefit in the treatment of lung cancer.